(untitled) - Egan, Jennifer (Anchor Books, 2011)
When a record executive hires a disturbed young woman, we get a glimpse into what has brought them to this point in their lives. Bennie Salazar, the record executive, is a washed up punk rocker. Sasha, his new employee, has secrets of her own. Everyone involved with their lives has a story. Author res: Brooklyn, NY Author tour. Previous titles: Emerald City; The Keep. 288pp BRODART CO., c2010.
Keywords: Punk rock musicians; Fiction; Sound recording executives and producers; Fiction; Older men; Fiction; Young women; Fiction